Quantifying determinants of social conformity in an online debating website. Issue 158 (February 2022) - Wijenayake, Senuri; Berkel, Niels van; Kostakos, Vassilis; Goncalves, Jorge
Highlights: Social conformity manifests in realistic online debating websites (31% conformity). Platform design impacts conformity, independent of group size and self-confidence. Individuals conform more when platform design promotes high social presence. Individuals conform more when challenged by larger group majorities. But platform design's emphasis on group composition shows no effect on conformity. Abstract: Social conformity is the act of individuals adjusting their personal opinions to agree with an opposing majority. Previous work has identified multiple determinants of social conformity in controlled laboratory studies, but they remain largely untested in naturalistic online environments. For this study, we developed a realistic debating website, which 48 participants used for one week. We deployed four versions of the website using a 2 ( high vs. low social presence) x 2 ( high vs. low emphasis on majority–minority group composition) between-subjects factorial design. We found that participants were significantly more likely to conform when the platform promotes high social presence, despite its emphasis on group composition. Our qualitative findings further reveal how different aspects of social presence embedded in platform design ( i.e., user representation, interactivity, and response visibility) contribute to heightened conformity behaviour. Our results provide evidence of the organic manifestation of conformity in online groups discussing subjective content and confirm the effect of platform design on online conformity behaviour. We conclude with a discussion on the implications of our findings on how future online platforms can be designed accounting for conformity influences.